The Role of the Prosecutor's Office in Prosecuting Criminal Acts of Sexual Harassment Against Minors (Case Study at the Semarang District Attorney's Office) - Rustaman, Viva Hari; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. The high number of cases of sexual harassment against minors is an important matter to be handled immediately, especially by the police as law enforcement officers, the prosecutor's office as law enforcement officers has various roles in criminal acts of sexual harassment against minors as in accordance with applicable laws and regulations. This study aims to determine, examine, and analyze the role of the Prosecutor's Office in prosecuting criminal acts of sexual harassment against minors at the Semarang District Prosecutor's Office, the obstacles and solutions of the Prosecutor's Office in prosecuting criminal acts of sexual harassment against minors at the Semarang District Prosecutor's Office, and the concept of the role of the Prosecutor's Office in prosecuting criminal acts of sexual harassment against minors in the Future. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data source used is primary data. While secondary data is obtained from literature study research consisting of primary legal materials, secondary legal materials, and testier legal materials. Based on the results of the study, it can be concluded that the role of the prosecutor's office in prosecuting criminal acts of sexual harassment against minors at the Semarang District Attorney's Office acts as a controller of the case process (Dominus litis) which also plays a role from the stage of receiving the transfer of case files from investigation to prosecution by considering aspects of child protection and justice based on the Criminal Procedure Code, Law Number 35 of 2014 concerning Child Protection, and Law Number 12 of 2012 concerning Criminal Acts of Sexual Violence. Obstacles and solutions for the prosecutor's office in prosecuting criminal acts of sexual harassment against minors at the Semarang District Attorney's Office, namely weak and inconsistent victim statements, lack of additional evidence, suboptimal coordination between law enforcement officers, social stigma and family intervention, lack of special prosecutors or special competence and solutions to overcome the obstacles experienced, namely by increasing the capacity and specialization of prosecutors, strengthening evidence through expert collaboration, encouraging a child-friendly trial system, utilizing the TPKS Law and child protection.